2018
DOI: 10.1186/s12974-018-1132-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of zinc-α2-glycoprotein suppressed seizures and seizure-related neuroflammation in pentylenetetrazol-kindled rats

Abstract: BackgroundZinc-α2-glycoprotein (ZAG) is a 42-kDa protein reported as an anti-inflammatory adipocytokine. Evidences from clinical and experimental studies revealed that brain inflammation plays important roles in epileptogenesis and seizure. Interestingly, closely relationship between ZAG and many important inflammatory mediators has been proven. Our previous study identified ZAG in neurons and found that ZAG is decreased in epilepsy and interacts with TGFβ and ERK. This study aimed to investigate the role of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…For the first time, we identified that ZAG increased glucose uptake in neurons. Interestingly, ZAG has been found to be decreased in epilepsy and has an anti‐epileptic effect (Liu et al., 2017, 2018; Wei et al., 2019). As glucose hypometabolism is known to be a trigger of epileptogenesis (Malkov et al., 2018; Samokhina et al., 2017), a ZAG decrease in epilepsy/seizure may be a metabolic mechanism of epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, we identified that ZAG increased glucose uptake in neurons. Interestingly, ZAG has been found to be decreased in epilepsy and has an anti‐epileptic effect (Liu et al., 2017, 2018; Wei et al., 2019). As glucose hypometabolism is known to be a trigger of epileptogenesis (Malkov et al., 2018; Samokhina et al., 2017), a ZAG decrease in epilepsy/seizure may be a metabolic mechanism of epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc‐α2‐glycoprotein (ZAG) is known to participate in glucose metabolism (Wei et al., 2019b) and has an anti‐epileptic effect (Liu et al., 2017, 2018). ZAG was found to be significantly decreased in the neurons of epilepsy patients, animal models, and a neuronal model, whereas over‐expressing ZAG alleviated seizures in epileptic rats (Liu et al., 2017, 2018; Wei et al., 2019). However, the mechanism by which ZAG regulates glucose metabolism and suppresses seizures remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Animals were raised in an SPF environment for 1 week prior to the start of the study and were kept in standard environmental conditions of temperature (26 ± 2°C), humidity (70%), and light (12 h/12 h light/dark). Adeno-associated virus (AAV) was injected into the caudal vein to establish mouse models of secretin knockdown and secretin overexpression [ 24 ]. The DNA sequence for secretin overexpression was combined with the AAV vector containing a green fluorescent protein (GFP) sequence, which was named the secretin overexpression group.…”
Section: Methodsmentioning
confidence: 99%
“…Transforming growth factor‐β (TGF‐β) and extracellular regulated protein kinase (ERK) pathway play key roles in inflammatory responses. It is demonstrated that ZAG may inhibit TGFβ‐mediated ERK phosphorylation 83 . Recent evidence suggests that ZAG inversely regulates liver inflammatory factors in human hepatocytes and NAFLD mice 63 (see Figure 3).…”
Section: Zinc‐alpha2‐glycoprotein Structure and Functionmentioning
confidence: 96%
“…It is demonstrated that ZAG may inhibit TGFβ-mediated ERK phosphorylation. 83 Recent evidence suggests that ZAG inversely regulates liver inflammatory factors in human hepatocytes and NAFLD mice 63 (see Figure 3).…”
Section: Zin C-alpha2-g Lycoprotein S Truc Ture and Fun C Tionmentioning
confidence: 99%